Effect of Different Types and Ratio of Fibers on the Tensile Strength of Reinforced Foam Concrete: A Review - Soran Abdrahman Ahmad; Azhar Jawad Nimat; Hersh F. Mahmood (Emerging Technologies and Engineering Journal)
Reducing the weight of buildings—particularly dead loads—is one effective way to lower construction costs. Foam concrete offers a viable alternative to conventional concrete for non-structural elements. This paper reviews the impact of incorporating polypropylene, natural fibers, steel fibers from waste tyres, and carbon fibers on the tensile strength of foamed concrete. According to the literature, the polypropylene content varied between 0.2% and 0.8%, with different target densities. Steel fibers extracted from scrap tyres ranged from 0.2% to 0.6%, while carbon fiber and Henequen fiber (natural fiber) were used separately or in combination with polymers in volumetric fractions ranging from 0.5% to 1.5%. The results presented in this paper indicate that tensile strength gradually increased as the volume of fibers increased up to a certain point, suggesting an optimal dosage for enhancing performance.